Censorship: Discord, Blocking of Discord (Russia) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Russia. Data sourced from CensoredPlanet.
Censorship Incident ID: RU-2024-0008. Severity: warning. Confidence: 75%